2016
DOI: 10.1001/jamainternmed.2016.2925
|View full text |Cite|
|
Sign up to set email alerts
|

ω-3 Polyunsaturated Fatty Acid Biomarkers and Coronary Heart Disease

Abstract: IMPORTANCEThe role of ω-3 polyunsaturated fatty acids for primary prevention of coronary heart disease (CHD) remains controversial. Most prior longitudinal studies evaluated self-reported consumption rather than biomarkers.OBJECTIVE To evaluate biomarkers of seafood-derived eicosapentaenoic acid (EPA; 20:5ω-3), docosapentaenoic acid (DPA; 22:5ω-3), and docosahexaenoic acid (DHA; 22:6ω-3) and plant-derived α-linolenic acid (ALA; 18:3ω-3) for incident CHD.DATA SOURCES A global consortium of 19 studies identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
246
3
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 356 publications
(267 citation statements)
references
References 51 publications
14
246
3
4
Order By: Relevance
“…Del Gobbo et al (1) demonstrate that a one standard deviation increase in the relative concentration of any of the omega-3 fatty acids in an accessible body compartment is associated with a roughly 10% reduction in risk of fatal CHD. Browning et al (7) report mean (+ standard deviation) concentrations of EPA and DHA in plasma phosphatidylcholine, the major plasma phospholipid, to be 1.1 + 0.5 and 3.2 + 1.2 % of total fatty acids, respectively.…”
Section: Omega-3 Fatty Acids and Cardiovascular Disease: What Was Alrmentioning
confidence: 99%
See 1 more Smart Citation
“…Del Gobbo et al (1) demonstrate that a one standard deviation increase in the relative concentration of any of the omega-3 fatty acids in an accessible body compartment is associated with a roughly 10% reduction in risk of fatal CHD. Browning et al (7) report mean (+ standard deviation) concentrations of EPA and DHA in plasma phosphatidylcholine, the major plasma phospholipid, to be 1.1 + 0.5 and 3.2 + 1.2 % of total fatty acids, respectively.…”
Section: Omega-3 Fatty Acids and Cardiovascular Disease: What Was Alrmentioning
confidence: 99%
“…A recently published study (1) provides new evidence that omega-3 fatty acids have a role in the primary prevention of coronary heart disease (CHD). This new publication included pooled data from 19 cohort studies conducted in 16 countries and including over 45,000 individuals with a median follow-up time of 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acids have relation to cardiovascular risks [3,[5][6][7]. Subanalysis of previous studies reported that administration of highly purified eicosapentaenoic acid (EPA) appeared to reduce the risk of recurrent stroke in a Japanese population of hypercholesterolemic patients receiving low-dose statin therapy [3,4].…”
Section: Discussionmentioning
confidence: 99%
“…Nyere biomarkør-studier støtter at et høyere inntak av flerumettet fett er forbundet med lavere risiko for koronar hjertesykdom [244][245][246][247] . Slike funn er imidlertid vanskelig å tolke og kan ikke «oversettes» til kvantitative råd om inntak ettersom studiene måler andeler av fettsyrer i vev.…”
Section: Biomarkører På Fettinntakunclassified